Educational Examination on the Role of Monetary Policies in Iran's Economic Resilience and Vulnerability to Booming Production - Yadegari, Mohsen (2021)
The objective of this study was to examination of the role of monetary policies (MP) in Iran's economic resilience (ER) and vulnerability for the production boom. In doing so, Iran's data was used for the period 2017-2018. A generalized method of moments (GMM) method was used to analyze the data, and all the analyses were done using Eviews10 software. The results indicate that MP and fiscal policy have affected the Iran ER index, so it is suggested that the government pave the way for strengthening the country's resilience by enhancing the efficiency of the country's monetary and financial system. The results indicated that MP and fiscal policy had affected Iran, so it is suggested that the country's economic policymakers try to design warning mechanisms to take action at the earliest opportunity to resolve the discrepancy in the event of any inconsistency in monetary and fiscal policies that make the country more vulnerable. Finally, the results indicated that MP and fiscal policy had affected net ER index of Iran; thus, it is recommended that the country's monetary and financial officials specify financial indices like the government's budget status and monetary indices like liquidity and bear in mind the consequences of these policies on the country's net ER.